2010
DOI: 10.2460/ajvr.71.3.374
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparison of plain radiography, double-contrast cystography, ultrasonography, and computed tomography for estimation of cystolith size

Abstract: Results indicated that measurements of cystolith size obtained by means of ultrasonography may overestimate the true size. This suggests that cystolith size estimates obtained by means of ultrasonography should be interpreted with caution whenever cystolith size may influence patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 21 publications
0
13
0
2
Order By: Relevance
“…Stone size was recorded as the largest diameter measured on either the lateral or ventrodorsal radiographic view, although these measurements may not reflect the true stone size because of radiographic magnification; however, Byl et al found that there was no difference in mean stone size among radiography, cystography, and CT, although there was a difference between these imaging modalities compared with stone measurement on abdominal ultrasound. As such, ultrasound reports were not used in our study to document stone size.…”
Section: Discussionmentioning
confidence: 99%
“…Stone size was recorded as the largest diameter measured on either the lateral or ventrodorsal radiographic view, although these measurements may not reflect the true stone size because of radiographic magnification; however, Byl et al found that there was no difference in mean stone size among radiography, cystography, and CT, although there was a difference between these imaging modalities compared with stone measurement on abdominal ultrasound. As such, ultrasound reports were not used in our study to document stone size.…”
Section: Discussionmentioning
confidence: 99%
“…While most dogs were imaged with radiography, a subset were imaged with ultrasonography. Ultrasonographic images overestimate cystolith size, and this might have introduced minor inaccuracies in urolith measurements 16 . Treatment regimens were also not standardized, as they were selected by the clinician managing the case at the time.…”
Section: Discussionmentioning
confidence: 99%
“…Für Urat-, Cystein- sowie Calciumphosphatsteine gilt das nicht. Ihr röntgenologischer Nachweis ist mit einer 25–27 % falsch negativen Quote behaftet, während diese Quote bei der Sonografie für alle Harnblasensteine, kompositions- und größenunabhängig, nur 3,4–6,5 % beträgt 29 . Röntgenologisch lassen sich aber insbesondere bei röntgendichten Materialien (Konkremente, Steine) Anzahl und Lage in der klinischen Routine sicherer bestimmen.…”
Section: Diskussionunclassified